Preferencia alimenticia y de oviposición de Gonipterus platensis(Coleoptera: Curculionidae) en tres especies comerciales de Eucalyptus en Colombia - Gamarra Bustamente, Julio (2024)
Gonipterus platensis (Marelli, 1926), is a beetle that belongs to the family Curculionidae, a phytophagous species within the genus Eucalyptus. It is native to Australia, where it is not considered a pest due to the presence of biological controllers. In Colombia, eucalyptus trees are the second exotic species with the largest planted area, and because in 2016 was recorded the presence of G. platensis in the country, efforts have been made to study and determine the potential damage that this species can cause in plantations through studies of its feeding preferences and oviposition, among others. The present study aims to determine the preference of G. platensis for the three most planted commercial eucalyptus species in the country: Eucalyptus grandis W.Hill ex Maiden, E. urophylla S.T. Blake, and the hybrid E. grandis W.Hill ex Maiden × E. urophylla S.T. Blake (E. urograndis). An experiment was conducted using a multiple-choice design to assess feeding and oviposition preference. Two assays were carried out: one with seedlings and the other with an olfactometer. The present study reveals that G. platensis has a feeding preference for E. grandis, followed by E. urophylla, and to a lesser extent, the hybrid species E. urograndis. Furthermore, G. platensis is capable of ovipositing in all three eucalyptus species studied without making any differentiation.